PERBEDAAN HASIL BELAJAR SISWA ANTARA YANG DIAJAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DENGAN YANG DIAJAR DENGAN MODEL PEMBELAJARAN LANGSUNGPADA MATERI POKOK FENOMENA ANTROPOSFER DAN ASPEK KEPENDUDUKAN - Baso, Wa Syarni (Universitas Halu Oleo, 2018)
This study aims to: 1) To know the significant difference between mean value of experiment class pree-test with pree-test control class. 2) To know the average value of the experiment class post-test is significantly better than the average value of post-test control class. 3) To find out the average value of experiment class gain is better than the average value of control class gain.Based on data analysis, it is concluded that: 1) There is a difference between the average of pree-test of the experimental class students with the average of pree-test of the control class students but not significant. This is indicated by the value of ttabe l <t count (1.142 <2.001). at Î± = 0.05. 2) There is a difference between the mean post-test of the experimental class students with the mean post-test of the control class students but not significant, which is shown by the t count <ttable (1.86 <2.001) at Î± = 0.05. 3) There is a difference between the N-gain of the experimental class students and the N-gain of the control class students but not significantly indicated by the t count <ttable (1.67 <2.001). at Î± = 0.05.